2013
DOI: 10.5812/ircmj.12719
|View full text |Cite
|
Sign up to set email alerts
|

Investigatingthe Effect of Pressure on Third Liver Point on Primary Dysmenorrhea: a Randomized Controlled Clinical Trial

Abstract: Background: Primary dysmenorrhea (PD) is a term used to describe uterine muscle spasms which occurs during the days of menstruation. Objectives: To determine the effect of acupressure on third liver point on primary dysmenorrhea. Patients and Methods: Female students living in dormitories of Kashan University of Medical Sciences in Iran who had PD were studied for three menstrual cycles between March till June 2012. Individuals with depression score higher than 19 according to the Beck-21 Depression scale were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Descriptive analysis showed that true acupressure can be an effective approach in managing postoperative and pregnancy-related nausea and/or vomiting, perioperative/prehospital pain, labor pain, sleep disturbances, respiratory disorders, anxiety, postoperative gastrointestinal dysfunctions and motion sickness. Studies on primary dysmenorrhea and chemotherapy-induced nausea and vomiting reported contradictory findings, where two studies [ 57 , 77 ] supported the superiority of true acupressure, while another two [ 17 , 64 ] stated no difference between groups. Results from a single study indicated that the true intervention was better than sham control in treating urodynamic stress incontinence [ 23 ], traumatic brain injury [ 24 ], cancer-related fatigue [ 16 ] and myocardial infarction-related nausea and vomiting [ 71 ], and in maintaining women’s general health [ 25 ] and stroke survivors’ cardiovascular functions [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive analysis showed that true acupressure can be an effective approach in managing postoperative and pregnancy-related nausea and/or vomiting, perioperative/prehospital pain, labor pain, sleep disturbances, respiratory disorders, anxiety, postoperative gastrointestinal dysfunctions and motion sickness. Studies on primary dysmenorrhea and chemotherapy-induced nausea and vomiting reported contradictory findings, where two studies [ 57 , 77 ] supported the superiority of true acupressure, while another two [ 17 , 64 ] stated no difference between groups. Results from a single study indicated that the true intervention was better than sham control in treating urodynamic stress incontinence [ 23 ], traumatic brain injury [ 24 ], cancer-related fatigue [ 16 ] and myocardial infarction-related nausea and vomiting [ 71 ], and in maintaining women’s general health [ 25 ] and stroke survivors’ cardiovascular functions [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…We did not find any study that evaluated the effect of acupressure at liv3 on anxiety. But our previous report[ 13 ] and Bazarganipour et al . 's study[ 12 ] showed decrease in dysmenorrhea after acupressure was performed on this point.…”
Section: Discussionmentioning
confidence: 84%
“…One of the energy-consuming organs of the liver meridian is genitalia,[ 11 ] and acupressure on the LIV3 can treat dysmenorrhea. [ 12 13 ] Although no study has been conducted about any change in anxiety occurring after acupressure on liv3 point, anxiety is associated with pain and pain relief may lead to an anxiety reduction. [ 14 ] Some studies have reported that acupressure can reduce dysmenorrhea[ 5 12 ] and the anxiety caused by dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…While, Kafaei-Atrian et al (2013) found that there is no significant difference between LIV3 and the placebo group in term of pain intensity in the third cycle. To address these issues, in our study, the acupressure protocol was started 3-7 days before menstruation (20 minutes per day) (26). In Kafaei-Atrian et al's study, acupressure was started by the onset of menstruation (less than 16 minutes per day) when pain had commenced.…”
Section: Discussionmentioning
confidence: 94%